War at the Top of the World : The Struggle for Afghanistan, Kashmir, and Tibet - Margolis, Eric S. (GHQ, Rawalpindi Army Education Publishing House, 2003)
"Focusing on the four nuclear powers, India, Pakistan, China, and Russia that converge in South Asia along oft-disputed borders created by the Himalayas, War at the Top of the World shows how long-held grudges over Afghanistan, Kashmir, Tibet, and other small territories could erupt into a full-scale nuclear confrontation."--Jacket.
Include Index
Keywords: Afghanistan -- Politics and government -- 1973-1989 -- China--Tibet Autonomous Region -- India--Jammu and Kashmir -- Politics and Government -- Jammu and Kashmir (India) -- Politics and government